The correlation between self-efficacy, care burden, and hopelessness of mothers with medical technology-dependent children: Medical Technology-Dependent Children (Journal of Medical Science, 2024)
Background. Having a child dependent on medical technology devices might cause some challenges for parents. Identifying these challenges and producing solutions may significantly contribute to the home care provider. This study aims to examine the correlation between self-efficacy, care burden, and hopelessness of mothers with medical technology-dependent children. Material and methods. This study was conducted using a cross-sectional and correlational design. Between April and July 2023, 164 mothers had at least one child receiving home care and were dependent on a medical technological device. The data were collected using an information form, the general self-efficacy scale, the Burden Scale for Family Caregivers, and the Beck Hopelessness Inventory. Results. It was found that the self-efficacy of mothers with a child dependent on a medical technological device was on the mean, their care burden was above the mean, and their hopelessness was below the mean. As the mothers’ self-efficacy increased, their hopelessness and care burden decreased. It was found that the mothers’ self-efficacy significantly predicted their care burden and hopelessness. Conclusions. In the hospital setting, it is necessary to initiate training, counselling, and psychosocial support for the caregivers and the entire family. Pediatric intensive care nurses play a significant role in achieving this.